Implementation of Character Education Management in Junior High Schools: Literature Review - Siregar, Julinda; Permatasari, Neli; Mardiyana, Hilda; Ambar, Kurniasari; Bada, Sitti Sastriana (Continuous Education: Journal of Science and Research, 2025)
Character education at the junior high school level is essential in shaping students' morals and personalities during their formative years. This study aims to explore various approaches, strategies, and best practices in managing character education in junior high schools through a narrative literature review. The urgency of this study arises from the increasing moral challenges faced by students and the need for schools to develop effective character-building frameworks. The research method involves a comprehensive literature review of 40 relevant articles published between 2019 and 2025, selected based on specific inclusion and exclusion criteria. Data were obtained from national and international scholarly databases, analyzed thematically to identify implementation patterns, supporting factors, and obstacles. The findings reveal that character education is effectively implemented through integration in curriculum content, school culture, religious activities, subject-based learning, extracurricular programs, and the involvement of families and communities. Teachers, especially guidance and counseling teachers, play a critical role in strengthening ethical behavior and responsibility among students. However, the implementation faces challenges such as lack of educator commitment, insufficient collaboration with families, and limited facilities. Innovative strategies, including pesantren-based approaches, school climate development, and personality modeling by teachers, are proven to enhance character formation. This review concludes that a comprehensive, collaborative, and well-managed approach is vital in optimizing character education outcomes in junior high schools.